ASPEK HUKUM TERHADAP KETERLAMBATAN PENDAFTARAN PEMBUATAN AKTA KELAHIRAN ANAK MENURUT UU NO. 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK DAN UU NO. 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Nur Febriatin (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTA human child who was born then his identity is not registered then will later get problems that will result in the state, government and society. Birth certificates will determine our fate later on. As an example in the Society if looking for work required birth certificate is concerned and if continue the school is also attached birth certificate, But the problem that happens that not everyone has birth certificate.For the sake of order in recording the data of the population, it is advisable to have a new family member immediately to be registered with the relevant Office in accordance with the mandate of the Act no later than 60 days after the birth. It is very important that children obtain public services from the Government and non-Government in the future.